Physical activity for longer working lives: an analysis of physical activity profiles of selected occupational groups in Poland - Biernat, Elzbieta; Buchholtz, Sonia; Góra, Marek (La Medicina del Lavoro, 2016)
Background: Extending working lives has become an inevitable objective of public policy in the era of population ageing. It is possible, however, that the duration of working life will depend on individual employability. Out of a wide range of factors affecting employability, in this paper we have analyzed one specific aspect of health status, which is physical activity. Methods: This paper studies the relationship between physical activity and BMI among representatives of seven occupational groups in Poland using a logit regression. We use a dedicated micro-database of over 5,000 Warsaw inhabitants. Results: Being overweight and obese is a significant problem among scientific researchers and public administration professionals; however, insufficient physical activity mainly affects sales workers and health professionals. Sex and age groups and professions are a far better predictor of a high BMI than the level of individual physical activity. In the case of the latter, the number of recreational disciplines and frequency of walking is more important than any other physical activity-related variable. We confirm that being overweight and having a sedentary lifestyle lead to a vicious circle of inactivity. Conclusions: In order to break this cycle or at least bring it under control, it is necessary to monitor the weight and waist circumference of workers, which is a prerequisite for any further intervention.